A Comparative Comparison of Khilāfa (Arabic: خلافة, caliphate) from the Point of View of Shaykh al-Ṣaduq and Ibn ʿArabī - Sayyid Muhammad Amin Derakhshani; Mahdi Azadparvar (آموزه‌‌های فلسفه اسلامي, 2023)
The issue of Khilāfa (Arabic: خلافة, caliphate) has been interpreted and elaborated in various fields of religious teachings and a comparative study of these views and creating a dialogue between them will help to emerge new works and results. Although both Shaykh al-Ṣaduq (Arabic: الشیخ الصدوق) and Ibn ʿArabī (Arabic: ابن عربی, Ibn ʿArabī‎) consider the caliph to have two heavenly and earthly sides and the caliph was the political, scientific and spiritual authority of society but selecting and making this position in the world of appearance (manifestation) is by divine will and outside people’s choice and the caliph in reality is the mediator of grace and the cause of the world’s survival but the theological attitude of Shaykh al-Ṣaduq and Ibn ʿArabī’s mystical tendency cause the differences between these two views, some of which are important and significant. For example, Shaykh al-Saduq considered the caliph to be derived from the divine attribute of “الانتصاف لأولیائه من أعدائه” and to prevent the creation of determinism in the world but Ibn ʿArabī introduced the caliph as the manifestation of the comprehensive name “Allāh” (Arabic: اللّٰه) and considered for the caliphate two real ranks and stages i.e. Muhammadan Reality and apparent i.e. human instances of saints. Ibn ʿArabī also distinguished between the caliphate of Allah and the caliphate of Rasūl (Arabic: رسول, God’s messenger) and introduced the caliphate of Allah as a political and scientific authority.